Role of isolated limb perfusion with recombinant human tumor necrosis factor α and melphalan in locally advanced extremity soft tissue sarcoma - Jakob, Jens; Hohenberger, Peter (Cancer, 2016)
The management of locally advanced extremity soft tissue sarcoma of the limbs is challenging, particularly for recurrent tumors and those adjacent to neurovascular bundles and joints. Typically, the tumors are large, below the fascia, and high-grade (T2b or stage III according to the American Joint Committee on Cancer) and thus require multimodal therapy. Treatment options must be tailored to patient and tumor characteristics. Isolated limb perfusion with recombinant human tumor necrosis factor α and melphalan (TNF-ILP) adds a therapeutic option to radiation therapy (RT) and systemic chemotherapy. Although the procedure is somewhat sophisticated to learn, it is a safe method and has been used now for almost 2 decades at more than 50 centers worldwide. TNF-ILP yields a high rate of complete or nearly complete pathologic tumor remission. In combination with surgical resection of the tumor remnant after isolated limb perfusion, the limb salvage rate is close to 90%. Often, patients can be spared adjuvant RT without long-term local tumor control rates being compromised. Nevertheless, TNF-ILP has never been compared with another treatment regimen in a randomized trial. This review summarizes the mode of action and standard application of TNF-ILP and focuses on a critical discussion of the role of TNF-ILP in the multimodal treatment of locally advanced primary and recurrent extremity sarcoma. Cancer 2016. © 2016 American Cancer Society. Cancer 2016;122:2624-2632. © 2016 American Cancer Society.
Gesehen am 06.08.2019
First published: 19 May 2016